Hekimler tarafından tutuklu veya hükümlülere tıbbi olmayan nedenlerle zorla ilaç verme - (:unkn) unknown (My University, 2009)
0
Forced use of medication by medical doctors on arrested persons or persons serving in prison for reasons other than medical treatment
Keywords: Hukuk